(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2023)
Hydroxyapatite (synthetic and biogenic) and based materials are widely used for treating bone fractures in orthopedics, traumatology, and dentistry due to their exceptional in properties and similarity in chemical composition to the mineral component of natural bone. Biogenic hydroxyapatite has higher bioactivity than synthetic hydroxyapatite due to its native chemical composition and porosity. Moreover, it can be efficiently and cost-effectively produced from natural sources. Biogenic hydroxyapatite from cattle bones and glass ceramics based on it created in Frantsevich Institute for Problems of Materials Science of NAS of Ukraine have been successfully used in practice by leading Ukrainian surgeons in the form of powder, granules, blocks, porous and dense ceramics, and bioadditives in orthopedics, traumatology, purulent-bone surgery, dentistry, for bone tissue in plastic surgery, and treatment of osteoporosis. Currently, the structure and properties of biogenic hydroxyapatite and glass ceramics have been modified by microwave sintering, foam replication method, and different additives like silicon, copper, iron, magnetite, etc. That allows for changing mechanical properties and resorption rate. However, using traditional methods of producing bioceramic implants requires additional technological operations to obtain specimens of the required shape and size. Additive manufacturing technology will allow the production of customized implants for each patient. Biogenic hydroxyapatite and glass ceramics based on it can be promising and low-cost materials for medical applications of 3D printing.